2013
DOI: 10.1007/s12192-012-0374-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of rapid and highly sensitive HSPA1A promoter-driven luciferase reporter system for assessing oxidative stress associated with low-dose photodynamic therapy

Abstract: Photodynamic therapy (PDT) is a regulatoryapproved modality for treating a variety of malignant tumors. It induces tumor tissue damage via photosensitizer-mediated oxidative cytotoxicity. The heat shock protein 70 (HSP70-1) is a stress protein encoded by the HSPA1A gene and is significantly induced by oxidative stress associated with PDT. The aim of this study was to identify the functional region of the HSPA1A promoter that responds to PDT-induced oxidative stress and uses the stress responsiveness of HSPA1A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…CCL5 gene is one of several chemokine genes clustered on the q-arm of chromosome 17. In Yin-Ling Lin et al [36,37] paper, the authors suggested that the antioxidant used in their work effectively suppressed CCL5 mRNA expression levels, indicating that oxidant may be involved in the induction of the CCL5 gene expression by dengue-2-virus infection. In our work we found that the transcription levels of this genes were decreased (p ≤ 0.05) after hazelnut consumption.…”
Section: Discussionmentioning
confidence: 97%
“…CCL5 gene is one of several chemokine genes clustered on the q-arm of chromosome 17. In Yin-Ling Lin et al [36,37] paper, the authors suggested that the antioxidant used in their work effectively suppressed CCL5 mRNA expression levels, indicating that oxidant may be involved in the induction of the CCL5 gene expression by dengue-2-virus infection. In our work we found that the transcription levels of this genes were decreased (p ≤ 0.05) after hazelnut consumption.…”
Section: Discussionmentioning
confidence: 97%
“…The classical transcription mechanism of genes belonging to HSP family is inducing HSFs binding to specific HSEs in promoter of HSP genes (Liu et al 1993). It is widely documented PDT-mediated oxidative stress could activate HSF binding activity almost instantaneously after PDT treatment (Gomer et al 1996;Zheng et al 2013;Luna et al 2000). Furthermore, it has been reported that PDT treatment will induce thermotolerance in treated cells, and the activation of HSF binding activity after PDT is partly correlated with the induction of thermotolerance (Gomer et al 1996;Fuchs et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…PDT treatment PDT treatment was performed as described previously (Zheng et al 2013). Cells were co-incubated with certain concentrations of photosensitizers in the dark at 37°C.…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations